2000
DOI: 10.1056/nejm200003023420904
|View full text |Cite
|
Sign up to set email alerts
|

Early Expression of Angiogenesis Factors in Acute Myocardial Ischemia and Infarction

Abstract: An increase in the level of HIF-1alpha is an early response to myocardial ischemia or infarction. This response defines, at a molecular level, one of the first adaptations of human myocardium to a deprivation of blood. HIF-1alpha is a useful temporal marker of acutely jeopardized myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
423
5
11

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(456 citation statements)
references
References 40 publications
13
423
5
11
Order By: Relevance
“…[9][10][11][12] EPCs are characterized by CD34, Flk-1, and CD133 antigen-positive cells, 13,14 and these cells are localized predominantly in the bone marrow. 15 In the peripheral circulation of adults, more mature, differentiated EPCs are found that are characterized by a decreased expression of CD133, are positive for VEGFR-2, and still express CD34.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] EPCs are characterized by CD34, Flk-1, and CD133 antigen-positive cells, 13,14 and these cells are localized predominantly in the bone marrow. 15 In the peripheral circulation of adults, more mature, differentiated EPCs are found that are characterized by a decreased expression of CD133, are positive for VEGFR-2, and still express CD34.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous angiogenic factors, including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (FGF-2), are naturally produced in response to tissue hypoxia and during wound healing. [1][2][3] This restorative process is, however, often insufficient to prevent tissue ischemia and necrosis, due in part to the slow kinetics and inadequate secretion of growth factors. Exogenous delivery of either VEGF or FGF-2 by single bolus injection has proven to be efficacious in stimulating localized angiogenesis and improving blood circulation in animal models of myocar-the distal, ischemic region of the flap.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found increased expression of HIF-α messenger RNA (mRNA) in hypoxic cultured cells and in organs (the retina and the lung) of animals exposed to short-term or long-term hypoxia [8,9]. Moreover, an early increase in the cardiac expression of HIF-1α has been observed in response to myocardial ischaemia or infarction in humans [10].…”
mentioning
confidence: 99%